Can HPV Test on Random Urine Replace Self-HPV Test on Vaginal Self-Samples or Clinician-Collected Cervical Samples? - Shih YH; Sun L; Hsu ST; Chen MJ; Lu CH (Dove Medical Press, 2023)
Yu-Hsiang Shih, Lou Sun, Shih-Tien Hsu, Ming-Jer Chen, Chien-Hsing Lu Department of Obstetrics and Gynecology, Taichung Veterans General Hospital, Taichung, TaiwanCorrespondence: Chien-Hsing Lu, Department of Obstetrics and Gynecology, Taichung Veterans General Hospital, 1650 Taiwan Boulevard Sect. 4, Taichung, Taiwan, Tel +886-4-23592525, Email chlu@vghtc.gov.twObjective: This study investigated whether random urine (RU) samples can be used to accurately identify human papillomavirus (HPV) and whether these samples can replace self-collected vaginal samples in HPV tests.Methods: A total of 167 patients with abnormal Pap smears were recruited. The patients provided self-collected vaginal and RU samples for HPV testing. Clinicians obtained cervical samples from the patients. Colposcopy examination and cervical biopsy were performed. Hybrid Capture II (HC II) and Cervista tests were used to detect HPV in the RU samples.Results: The results of tests on clinician-collected cervical samples were used as the benchmark. The sensitivities of the Cervista tests on vaginal samples and the HC II and Cervista tests on RU samples were 75.00%, 49.07%, and 44.44%, respectively. After we adjusted the HPV detection cutoff value for urine samples based on values in the receiver operating characteristic curve, the sensitivities of the HC II and Cervista tests increased to 63.89% and 58.33%, respectively. In 167 patients, 59 had cervix biopsies showing CIN2 or worse (CIN2+). For CIN2+, the sensitivity was 47.5% and 50.8% in the HC II and Cervista tests on RU samples, respectively.Conclusion: HPV tests on RU samples had approximately 60% sensitivity to HPV tests on clinician-collected cervical samples after the cutoff values were adjusted. For CIN2+, the sensitivity was only approximately 50%. Further studies and improvements in urine-based HPV testing are needed to establish it as a more convenient and accessible method for detecting HPV and cervical dysplasia in patients.Keywords: HPV, random urine, vaginal HPV test, cervical intraepithelial lesion, Hybrid Capture II, Cervista